1977
DOI: 10.1001/archderm.113.5.648
|View full text |Cite
|
Sign up to set email alerts
|

Osler node, Janeway lesions, and splinter hemorrhages

Abstract: This report documents the occurrence of an Osler node, subungual hemorrhages, and Janeway lesions peripheral to an infected arterial catheter. A brief review of these dermatological manifestations of infection is given and the importance of surgical removal of the involved artery after poor response to medical therapy is stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…39 Emboli and direct invasion of blood vessels present as generalized maculopapular lesions, which evolve rapidly, or as widespread purpuric lesions. Septic embolization can cause Osler's node, Janeway lesions, [40][41][42][43] petechiae, and splinter hemorrhages. 44 We found that the most frequent cutaneous signs were purpuric nonblanching lesions and petechiae.…”
Section: Discussionmentioning
confidence: 99%
“…39 Emboli and direct invasion of blood vessels present as generalized maculopapular lesions, which evolve rapidly, or as widespread purpuric lesions. Septic embolization can cause Osler's node, Janeway lesions, [40][41][42][43] petechiae, and splinter hemorrhages. 44 We found that the most frequent cutaneous signs were purpuric nonblanching lesions and petechiae.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective chart review of over 12 500 patients undergoing radial artery catheterization revealed only six cases of pseudoaneurysm formation (an incidence of 0.048%) [2]. The occurrence of an infected radial artery pseudoaneurysm after arterial catheterization is very rare, with only 21 previous reports in the English-language literature over the last 50 years [2,[5][6][7][8][9][10][11][12][13][14]. Only one report of a haemophiliac patient developing a pseudoaneurysm of the radial artery could be found on searching, and this was not infected [15].…”
Section: Discussionmentioning
confidence: 99%
“…Osler nodules are red-purple, painful nodules often with a pale center and usually located on fingers and toes. [6][7][8] They have been reported to be associated with subacute/chronic forms of embolic diseases, most commonly bacterial endocarditis. 9 Janeway lesions, first described by Janeway more than 100 years ago have been associated with acute bacterial endocarditis.…”
mentioning
confidence: 99%